Effect of Carrot and Sweet Potato on the Storability of Chicken Nuggets during Refrigeration Storage - Bhosale, S. S.; Biswas, A. K.; Sahoo, J.; Chatli, M. K.; Sharma , D. K.; Devatkal, S.K. (Journal of Meat Science, 2011)
Chicken meat nuggets were prepared with ground raw carrot (10%) and mashed sweet potato (10%), individually aerobic packaged and stored at 4±1°C. Samples were evaluated for pH, free fatty acid (FFA) contents, 2-thiobarbituricacid reacting substances (TBARS), microbiological quality and sensory pro files at 5 days intervals during 25 days storage. Nuggets formulated with carrot and sweet potato affected (P
Keywords: Lipid oxidation; carrot; sweet potato; chicken nuggets